Using ICTs to eradicate the Carambola fruit fly - Mathur, Shantanu (Technical Centre for Agricultural and Rural Cooperation, 2003)
An IFAD project aimed at eradicating the Carambola fruit fly in Suriname and French Guiana is using satellite technology to effectively target infested areas.